Error reduction in the finite helical axis for knee kinematics - Bishop, E. L.; Küpper, J. C.; Fjeld, I. R.; Kuntze, G.; Ronsky, J. L. (Computer Methods in Biomechanics and Biomedical Engineering, 2018)
Traditionally the FHA is calculated stepwise between data points (sFHA), requiring down sampling to achieve a sufficiently large step size to minimize error. This paper proposes an alternate FHA calculation approach (rFHA), using a unique reference position to reduce error associated with small rotation angles. This study demonstrated error reduction using the rFHA approach relative to the sFHA approach. Furthermore, the rFHA in the femur is defined at each time point providing a continuous representation of joint motion. These characteristics enable the rFHA to quantify small differences in knee joint motion, providing an excellent measure to quantify knee joint stability.